2021
DOI: 10.1186/s12893-021-01243-x
|View full text |Cite
|
Sign up to set email alerts
|

Long-term follow-up of prophylactic mesh reinforcement after emergency laparotomy. A retrospective controlled study

Abstract: Background Prevention of incisional hernias with a prophylactic mesh in emergency surgery is controversial. The present study aimed to analyze the long-term results of prophylactic mesh used for preventing incisional hernia after emergency midline laparotomies. Methods This study was a registered (NCT04578561) retrospective analysis of patients who underwent an emergency midline laparotomy between January 2009 and July 2010 with a follow-up period … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…13 The possibility of Zenker's degeneration, a prototype of coagulative necrosis of skeletal muscle such as the rectus abdominis, which can occur in severe toxaemia as in typhoid fever. 25 Previous observational studies & RCTs which have shown PMP effective in reducing incisional hernia after EML 59 have included a wide spectrum of aetiology (including cases without peritonitis), unlike our study which included only patients undergoing EML for intestinal perforation. Obesity is probably the most important risk factor for incisional hernia, and up to 73% of Western population are overweight. 26 Thus, Western trials which may have a large proportion of such patients may show a greater ‘benefit’ from PMP, unlike our cohort of patients which more accurately reflect the population of LMICs.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…13 The possibility of Zenker's degeneration, a prototype of coagulative necrosis of skeletal muscle such as the rectus abdominis, which can occur in severe toxaemia as in typhoid fever. 25 Previous observational studies & RCTs which have shown PMP effective in reducing incisional hernia after EML 59 have included a wide spectrum of aetiology (including cases without peritonitis), unlike our study which included only patients undergoing EML for intestinal perforation. Obesity is probably the most important risk factor for incisional hernia, and up to 73% of Western population are overweight. 26 Thus, Western trials which may have a large proportion of such patients may show a greater ‘benefit’ from PMP, unlike our cohort of patients which more accurately reflect the population of LMICs.…”
Section: Discussionmentioning
confidence: 96%
“…Previous observational studies & RCTs which have shown PMP effective in reducing incisional hernia after EML 59 have included a wide spectrum of aetiology (including cases without peritonitis), unlike our study which included only patients undergoing EML for intestinal perforation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Systematic abdominal wall closure with small bites (SB) technique significantly reduces fascial dehiscence (FD) (6.6% vs. 3.8%) 6 and IH (27% vs. 15%) (18) in emergency laparotomy. Moreover, the use of PM in these situations, especially in the presence of other risk factors, reduces even more the incidence of FD and IH (19)(20)(21).…”
Section: High-risk Related Situations Emergency Laparotomymentioning
confidence: 99%
“…These same long-term results were previously observed in other similar works [ 15 ]. Moreover, when it comes to preventing IH with non-absorbable synthetic mesh after emergency midline laparotomy, the scarce long-term follow-up data also show a similar phenomenon where the mesh only delays the onset of the hernia [ 16 ]. Finally, it is interesting to note that other studies concerning the closure of the abdominal wall, where the efficacy of meshes in the treatment or prevention of IH is not evaluated, reveal similar curves.…”
mentioning
confidence: 99%